A case study of construction dispute – case A & B - Hoei, Susanty. (2013)
Construction projects usually involve high cost and expensive machineries. Most of the time, construction works are done with the collaboration of one main contractor and one or several subcontractors. When a certain portion of the construction work is completed, the subcontractor would normally submit a monthly payment claim to the main contractor. This payment claim is crucial for the subcontractor to keep his operation and activities going. A delay in payment from the main contractor will cause the subcontractor to suffer because of the hefty amount of money he has put in for the construction work. When a dispute regarding this payment occurs or when there is a dispute on contractual matter, an Act needs to aid in achieving a quick dispute resolution. In the past, Singapore did not have any law or Act that provided a fast track for dispute resolution in the construction industry. The legal firms handling the dispute cases were usually ill equipped with technical words used in the construction industry. As a result, the conflict resolution was a long and costly process. This led to a long delay in the construction project involved and the party with the outstanding payment could ill afford the case dragging and his progress payment not paid. This report will focus on a case dispute involving some fundamental issues frequently encountered between a domestic subcontractor and the main contractor. The focused case study will be analyzed in great details with frequent references to relevant journals and articles. Discussions on some precedent case studies and evaluations into the Building and Construction Industry Security of Payment Act in Singapore will also be done in this report. At the end of the report, some consolidated conclusions and recommendations will be presented.